“Delizioso Caffè Da Dessert” / Amirul Eiqmal Afif Mahmud Munir - Mahmud Munir, Amirul Eiqmal Afif (2019)
The business name is Delizioso Caffè Da Dessert. The name was inspired by the taste of delicious of the creamy of pudding and ice cream that would make everyone mouthwatering just by hear the name of it. The dessert is made with milk, cream, various sugars, and flavouring such as fresh fruit and nut purees. The taste is very incredible and that is what make our product will be. As for the nature of the business, we are producing pudding as our main activities. We produced various type of pudding such as tapioca pudding, vanilla pudding, panna cotta, tropicana pudding, chocolate pudding, banana pudding and not to forget our main flavour that is widespread around the world about how the taste it is which Cotton Candy Freezy Pudding Ice Cream.